Exploratory research on therapeutic agents combined with early diagnostic biomarkers for colorectal cancer - Liao, Qiming; Xue, Yulong; Yu, Yajiang; Liu, Mengzhe; Yu, Zeyuan; Cheng, Xiaoxia; Zhang, Lei; Ji, Xinying (Frontiers in Pharmacology, 2026)
IntroductionColorectal cancer (CRC) remains a leading cause of cancer-related mortality worldwide. Although diagnostic and therapeutic strategies have advanced, the molecular mechanisms driving CRC pathogenesis are not fully understood, highlighting the need for novel biomarkers and therapeutic agents.MethodsIntegrated bioinformatics analyses of transcriptomic datasets from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) were performed to identify survival-associated differentially expressed genes (DEGs) in CRC (|log2FC| > 1.5, p < 0.05). These key DEGs were then used to query the L1000FWD, DGIdb, and CMap platforms to predict candidate small-molecule drugs. The top candidate was evaluated by molecular docking, and its anti-tumor effects were validated by MTT cell viability assays in CRC cell lines. ResultsWe identified 15 survival-associated DEGs—MELK, NFE2L3, MCM2, MAD2L1, AUNIP, CXCL3, GLDN, GREM2, ALDH1A1, CILP, FABP4, AOC3, CNN1, ANGPTL1, and DES—as potential early diagnostic biomarkers for CRC. Drug-repositioning analyses convergently highlighted SB-225002 as a promising therapeutic agent. Molecular docking showed high binding affinity of SB-225002 to multiple key targets. MTT assays demonstrated that SB-225002 exerted dose-dependent inhibitory effects on the proliferation of CRC cell lines (SW-480, DLD-1, and MC38), with IC50 values of 2.307 μM, 0.9456 μM, and 3.449 μM, respectively.DiscussionThis study systematically delineates a novel panel of early-detection biomarkers for CRC and identifies SB-225002 as a repurposed candidate therapeutic agent. The integrative strategy combining multi-cohort transcriptomic analysis, drug-repositioning platforms, molecular docking, and experimental validation offers a feasible framework for discovering clinically actionable biomarkers and small-molecule therapies for CRC.